2010
DOI: 10.1371/journal.pcbi.1000950
|View full text |Cite
|
Sign up to set email alerts
|

Systems Biology of Coagulation Initiation: Kinetics of Thrombin Generation in Resting and Activated Human Blood

Abstract: Blood function defines bleeding and clotting risks and dictates approaches for clinical intervention. Independent of adding exogenous tissue factor (TF), human blood treated in vitro with corn trypsin inhibitor (CTI, to block Factor XIIa) will generate thrombin after an initiation time (Ti) of 1 to 2 hours (depending on donor), while activation of platelets with the GPVI-activator convulxin reduces Ti to ∼20 minutes. Since current kinetic models fail to generate thrombin in the absence of added TF, we implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
197
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(201 citation statements)
references
References 98 publications
3
197
0
1
Order By: Relevance
“…38 Our results indicate that cAMP elevation is more effective than COX-1 or P2Y 1 inhibition under these conditions. The multiscale and patient-specific modeling presented here extends earlier modeling efforts of platelet function and/or coagulation 20,21,[39][40][41][42] by including a highly robust description of intracellular platelet signaling through GPVI, P2Y 1 , TP, and IP. To our knowledge, our NN/multiscale model is the first such approach to make donor-specific predictions of platelet function under flow in the presence of both released ADP and thromboxane and pharmacologic modulators of clinical relevance.…”
Section: Discussionmentioning
confidence: 81%
“…38 Our results indicate that cAMP elevation is more effective than COX-1 or P2Y 1 inhibition under these conditions. The multiscale and patient-specific modeling presented here extends earlier modeling efforts of platelet function and/or coagulation 20,21,[39][40][41][42] by including a highly robust description of intracellular platelet signaling through GPVI, P2Y 1 , TP, and IP. To our knowledge, our NN/multiscale model is the first such approach to make donor-specific predictions of platelet function under flow in the presence of both released ADP and thromboxane and pharmacologic modulators of clinical relevance.…”
Section: Discussionmentioning
confidence: 81%
“…While some new models in blood rheology (notably the ones in [18,20,23]) have appeared, the thrust of development is in simulation of such models in the complex geometries of the vasculature/medical devices through which blood flows. With regard to clot formation, the acceptance of in silico tests for the generation of hypotheses by an influential section of the biochemical community (see Mann [51]) has meant increasingly comprehensive single-scale models of coagulation (notably the ones in [36,37]). Simultaneously, with our understanding of in vivo coagulation evolving from the "cascade" model into a 'three-stage multi-scale process made functional by flow', multi-scale models of coagulation have been developed (notably the ones in [40,41,48]), simulated in the presence of flow, and their predictions verified with experimental hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…Luan et al [35] used a single scale heterogeneous model to show that mathematically-determined points of fragility coincided with clinical data, and thus advocated the use of such models for determining therapeutic targets. Chatterjee et al [36] extended the model of [30] and developed a single-scale pseudo-homogeneous model that captured the clot initiation that occurred in blood even when treated with corn trypsin inhibitor (Corn trypsin inhibitor is used to block the contact pathway of coagulation). Susree and Anand [37] combined elements of the models in [30,32,34] to come up with a single scale pseudo-homogeneous model which showed that inhibition of platelet activation by other platelets had a much more significant effect on thrombin production than inhibition of platelet activation by thrombin.…”
Section: Single-scale Modelsmentioning
confidence: 99%
“…Mechanistic ODE coagulation models from our laboratory [23,24] were built upon the earlier studies of Jones and Mann [25], Hockin et al [26], and later Butenas et al [27] who developed and then subsequently refined highly mechanistic coagulation models. Other laboratories have also expanded upon Hockin et al for example by exploring the intrinsic pathway, the role of stochastic fluctuations in coagulation [28], and the dynamics of thrombin mediated clot formation [29] and fibrinolysis [30]. Other aspects of coagulation have also been modeled, such as platelet biochemistry [31], multi-scale models of clot formation [32,33], and transport inside clots [34].…”
Section: Introductionmentioning
confidence: 99%